The Urgency of Guidance and Counseling in Dealing with Students' Spiritual and Emotional Intelligence Problems - Hamidah, Siti; S, Irwan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aimed to determine the urgency of Guidance and Counseling in overcoming problems related to the spiritual and emotional intelligence of students at MAN 3 Langkat. This type of research is descriptive qualitative research with a case study approach. The research location is MAN 3 Langkat. The sample population of this study amounted to 8 students selected by the counseling guidance teacher MAN 3 Langkat with certain provisions. These namely students need help with spiritual intelligence and emotional intelligence at MAN 3 Langkat. Data collection techniques used in this study are observation, interviews, and documentation. Data analysis used is data reduction, data presentation, and verification and uses triangulation as a credibility test with source triangulation. From this research, it is concluded that the urgency of counseling in dealing with the problems of spiritual intelligence and emotional intelligence of students significantly influences students. The impact of delay in handling these problems Guidance and Counseling is feared that students will dissolve in these problems, and it is increasingly difficult to be guided. In contrast, if guidance and counseling have timeliness in handling it, it will positively impact students. This is evidenced by the behavior displayed by students, namely having awareness and commitment to worship and the ability to motivate themselves and control their emotions.